Therapeutic effect of mefloquine on Schistosoma mansoni in experimental infection in mice - Abou-Shady, Omaima Mohammed (J Parasit Dis, 2014)
Schistosomiasis is one of the most prevalent parasitic infections worldwide. Praziquantel is the drug of choice for treatment of schistosomiasis for its high efficacy. The present work was carried out on 160 mice to evaluate the therapeutic effect of mefloquine on experimental schistosomiasis mansoni. Mice were classified into 3 groups; group I (20 infected non-treated mice), group II included 60 infected mice which were further divided into group IIm (20 mice treated with 400 mg/kg mefloquine), group IIp (20 mice treated with 1,000 mg/kg/2 days praziquantel) and group IIpm (20 mice treated with 200 mg/kg mefloquine and 500 mg/kg praziquantel), group III included 80 non-infected mice subdivided into group IIIn (20 non-treated mice), group IIIm (20 mice treated with 400 mg/kg mefloquine), group IIIp (20 mice treated with 1,000 mg/kg/2 days praziquantel), group IIIpm (20 mice treated with 200 mg mefloquine and 500 mg praziquantel). Mefloquine significantly reduced worm burden, tissue egg load, number of liver granulomas and increased the percent of dead ova within granulomas. Combination of mefloquine and praziquantel gave better curative effects than praziquantel or mefloquine given alone.